2009
DOI: 10.2147/vhrm.s6804
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of heart failure in a Nigerian teaching hospital

Abstract: BackgroundCongestive cardiac failure (CCF) has emerged as a major public health problem worldwide and imposes an escalating burden on the health care system.ObjectiveTo determine the causes and mortality rate of CCF in the University of Port Harcourt Teaching Hospital (UPTH), south Nigeria, over a five-year period from January 2001 to December 2005.MethodsA retrospective study of CCF cases were identified from the admission and discharge register of the medical wards of UPTH and the case notes were retrieved f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 20 publications
(23 reference statements)
4
32
2
Order By: Relevance
“…In this study, HIV cardiomyopathy and cor pulmonale are represented as aetiologic factors in heart failure, not mentioned in previous studies conducted in urban areas of Cameroon and some countries of sub-saharan Africa [13,15,16], and mentionned in very high percentages by Magulaa NP and Mayosi BM [17,18] in studies carried out in south Africa. They stated that cardiac involvements in human immunodeficiency virus (HIV) infection, cor pulmonale, and pericarditis contribute to over 20% of cases of heart failure.…”
Section: Discussionmentioning
confidence: 56%
“…In this study, HIV cardiomyopathy and cor pulmonale are represented as aetiologic factors in heart failure, not mentioned in previous studies conducted in urban areas of Cameroon and some countries of sub-saharan Africa [13,15,16], and mentionned in very high percentages by Magulaa NP and Mayosi BM [17,18] in studies carried out in south Africa. They stated that cardiac involvements in human immunodeficiency virus (HIV) infection, cor pulmonale, and pericarditis contribute to over 20% of cases of heart failure.…”
Section: Discussionmentioning
confidence: 56%
“…In the Abeokuta heart failure (HF) registry, hypertension was responsible for 78.7% of HF in the city. It was also responsible for 62.6%, 56.3%, 57% and 44.1% of heart failure cases in Abuja [148] , Port Harcourt [149] , Jos [150] and Uyo [126] respectively. In the recently published transnational study of HF in sub-Saharan Africa, hypertension was clearly shown as the predominant cause of HF in the region, especially in Nigeria.…”
Section: Conduction Abnormalitiesmentioning
confidence: 99%
“…[18] Ntusi and Mayosi noted that the situation was in flux, as risk factors for cardiac disease such as diet, lifestyle and cultural attitudes were changing as a consequence of rapid urbanization in developing countries. [13] More recently, Sliwa and Mayosi, reviewing the THESUS-HF data published in 2012 [25] noted that an epidemiologic transformation had occurred in the mid 2000's characterized by a clear increase from 23 to 45% in the prevalence of hypertension as the cause of heart failure, an increase in the frequency of dilated cardiomyopathy from 20-30%, a reduction in the number of rheumatic valvulopathies from 22 to 14%, and an increase in the frequency of ischemic cases from 2 to 8%.…”
Section: Accepted Manuscriptmentioning
confidence: 99%